Energy-driven refurbishment of existing buildings: review and a solution framework. (2017) - Srour, Issam; Khaddaj, Maggie; Saab, Mario
Population growth, rapid economic development, and urbanisation have increased the demand for energy worldwide leading to increased levels of CO2 emissions, and, consequently, contributing to global warming. More than 40% of this energy is consumed in buildings. Assessing energy performance of existing buildings with the goal of determining an optimal rehabilitation strategy offers a chance to reduce the rising demands for energy. Several studies have advocated and demonstrated the energy savings from energy-driven renovations of existing commercial and residential buildings. This paper builds on these studies by developing a framework for completing renovation projects of existing buildings. The theoretical framework is generic in nature and can be applied to any facility that is looking for ways to enhance its energy efficiency. Implementing the framework is expected to lead to significant savings in energy consumption, resulting in both economic and environmental benefits.